Pemanfaatan Bahan Ajar Lembar Kerja Siswa (LKS) UntukMeningkatkan Efektifitas Pembelajaran PendidikanAgama Islam Kelas VII Di Sekolah Menengah Pertama (SMP)Muhammadiyah 2 Surakarta - Prakoso, Enggar Bondan; , Dra. Chusniatun, M.Ag (2016)
In the process of learning the teacher must be able to convey the subject matter well in accordance with the theme or the appropriate chapter students' abilities. With teaching materials student worksheet (LKS) will help teachers deliver lessons so that the material given to the students on target. The use of student worksheet (LKS) helps students to learn everyday both in school and at home, because the student worksheet (LKS) is designed to enable students to learn wherever comfortable existence. To realize the teaching and learning activities fun then the teacher must have the skills in presenting the material, condition the classroom and effective teaching and learning process is assisted by student worksheet (LKS). This study assesses about: Teaching Material Utilization student worksheets to improve the effectiveness of teaching Islamic education classes VII School (SMP) Muhammadiyah 2 Surakarta. This research is a field with a qualitative approach means is that this research requires the author to jump directly spaciousness and interacts directly to obtain valid and accurate data as needed. This data collection techniques using interviews, observation, and documentation. While technical analysis of the data used is descriptive qualitative with the deductive method, which is a way of thinking by reviewing the study of theory and then attributed to the fact or facts obtained in the field by reasoning, then drawn a conclusion. The results of this study indicate that the use of student worksheet (LKS) (1) on teaching and learning activities in class on the subjects of jurisprudence, the students enjoy the learning process that has tersetruktur and students are also much easier to learn when you're at home or at school. In addition to the student worksheet (LKS) teacher of Islamic education easier in menyapaikan material although it should provide additional material that is not in (LKS), (2) the utilization of student worksheet (LKS), the students easier to accept, understand and mastering the content of the subject matter of education Islam (PAI) in chapter taharah, (3) utilization of teaching materials student worksheet (LKS) may increase the effectiveness of learning jurisprudence class, because the use of student worksheet (LKS) (a) students easily master learning materials for students have more time to learn in class and studying at home, (b) students feel happy in the learning process in class in accordance with plans made teachers plan learning process (RPP), (c) the students were delighted to learn in school, ( d) students become obedient to the rules that exist in schools, (e) the teacher becomes more easily convey the material in class, addition (e) teachers also get good results from the learning process a fun class.